Isolation Set-up and Characterization of cancer stem cells from HT29 colon cancer cell line - Pooneh Mokarram (Shiraz University of Medical Sciences, 2021)
Abstract Background: Cancer stem cells (CSCs) have critical roles in tumor initiation, progression, metastasis, resistance to chemoradiotherapy, and recurrence in various cancers such as colon cancer. Therefore, extensive studies are required to understand the CSCs mechanism of action and design novel cancer therapies. Successful isolation and characterization of CSCs from tumor tissues or cancer cell lines provide the proper opportunity for these kinds of studies. This study aimed to isolate and characterize CSCs from HT29 colon cancer cell lines. Methods: Sphere formation assay was used to isolate CSCs from the HT29 cell line. The expression of four stemness genes, including LGR5, SOX2, c-Myc, and Oct4, was assessed by real-time PCR. The CSC markers, CD 44 and CD 24, were also evaluated and compared between the parental HT29 cell line and HT29-derived spheres by flow cytometry. Statistical analysis was performed using GraphPad Prism version 6.0 and the Mann-Whitney U test. Results:HT29-derived sphere cells were successfully formed in serum-free media. The proportion of CD 24 and CD 44-expressing cells and the expression of LGR5, SOX2, c-Myc, and Oct4 stemness genes were significantly higher in CSCs isolated from HT29 spheres compared with parental HT29 cells. Conclusion:Sphere formation assay is a proper method for the isolation of CSCs from the HT29 cell line. The stemness markers LGR5, SOX2, c-Myc, Oct4,CD 44,andCD 24are suitable for the characterization of these cells.